Digital Distraction pada Mahasiswa: Implikasi untuk Desain Pembelajaran dan Kurikulum Pendidikan Tinggi - Dariyono Dariyono; Muhammad Faizal Rizky (JOURNAL SAINS STUDENT RESEARCH, 2026)
The rapid development of digital technology has significantly impacted learning in higher education, including the rise of digital distraction among university students. This theoretical review aims to integrate various concepts, models, and empirical findings related to digital distraction based on relevant literature. The study employed a theoretical review approach by analyzing articles addressing classroom distraction frequency, self-regulation mechanisms, and the dimensions of the Smartphone Distraction Scale (SDS). The synthesis reveals that digital distraction unfolds through a multilayered cycle beginning with digital stimuli, attention shifts, increased cognitive load, and reduced self-regulation, ultimately affecting academic performance. This review proposes the conceptual model of the Digital Distraction Cycle as a theoretical contribution explaining how digital distraction occurs among students and offers practical implications to support educators in designing learning strategies and self-regulation interventions that are more adaptive to digital-era challenges..